Результати і сучасний стан інтродукції декоративних та раритетних видів рослин в умовах Національного дендрологічного парку “Софіївка” НАН України - Kosenko, I.S.; Golub, N.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The article presents the results of introducting of dif ferent species of plants. It points out ecological and biological peculiarities of rare species – Trapa natans L. s.l. in National Dendrological Park Sofiyivka of the NAS of Ukraine. It offers practical recommendations for using this species in decorating of ponds.